Large scale water manipulation experiment in the Arctic tundra - Walter C. Oechel; Donatella Zona (Arctic Data Center)
This data set includes data from the Barrow Environmental Observatory (BEO) as part of the National Science Foundation (NSF) Biocomplexity Program. This involved increasing and decreasing the water table over large areas of tundra and observing the effects over the diverse microtopography of the region. It also includes measurements from the drained section (BEC) and flooded section (BEN) of Cake Eater Lake. Note: Files were updated on 04 Jan 12. Most of the data are the same (with same units) but in all years now photosynthetically active radiation (PAR) has been replaced by incoming shortwave global solar radiation in the spectral range from 310 to 2800 nm (unit is Wm-2). This radiation for 2006-2008 is from the BEC tower, while for 2005: from 1 to 29 July the radiation is from ARM-Barrow and after the 29 July until the end of August is again from BEC. Because the ARM site is closer to the coast from the BE sites and it is more cloudy a regression of the data from 1-29 July was performed to match conditions at the BE.